Influenza del trattamento della schizofrenia con neurolettici tipici o olanzapina sui costi sanitari e sugli outcomes lavorativi - Barioglio, Angelomarco; Guidi, Luca; Mariani, Giorgio (Farmeconomia. Health Economics and Therapeutic Pathways, 2005)
The aim of the present study was to evaluate the global treatment cost of schizophrenia with olanzapine or typical neuroleptics, according to Local Health Care Unit point of view. This analysis was performed through naturalistic observation of a cohort of schizophrenic patients referring to Ascoli Piceno ASL Department of Mental Health during 4 years (2001-2004). During year 2003, investigators have identified a cohort of patients who were undergoing treatment switch from typical neuroleptics to olanzapine. These patients, after the switch, are observed prospectively for the next 2 years and retrospectively for the last 2 years of treament. This method allow us to collect data about 4 years of treatment: 2 years of typical neuroleptic treatment followed by 2 years of olanzapine treatment. The present work is presenting the analysis of the first 3 years of observation. The results of our analysis are demonstrating that olanzapine treatment, through a better patient-physician alliance and with rehabilitative activities, allow lower total medical costs for the treatment of schizophrenia than typical neuroleptics. The higher acquisition cost of olanzapine versus typical neuroleptics was compensated by less hospitalizations and territorial medical interventions. During olanzapine treatment patients followed more rehabilitative activities (+71,26%, p